Urban spatial policy: a European gender perspective - GREED, Clara H. (European Spatial Research and Policy, 1996)
The gender dimensions of urban form and town planning policy are investigated drawing on findings from research on 'women and town planning' in Britain, and making comparisons with the wider European situation. Even if women do have different policies this is irrelevant if they are not represented in decision-making groups. Therefore the representation of women in the built environment professions and urban policy making levels is discussed. lt is argued that in order to change spatial policy it is essential to increase women's participation in town planning, and to make the consideration of gender issues a required component of policy-making.